2018
DOI: 10.1155/2018/8604718
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Tryptophan Levels as an Indicator of Global Cognitive Performance in Nondemented Women over 50 Years of Age

Abstract: Aging is a physiological decline process. The number of older adults is growing around the world; therefore, the incidence of cognitive impairment, dementia, and other diseases related to aging increases. The main cellular factors that converge in the aging process are mitochondrial dysfunction, antioxidant impairment, inflammation, and immune response decline, among others. In this context, these cellular changes have an influence on the kynurenine pathway (KP), the main route of tryptophan (Trp) catabolism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 70 publications
(69 reference statements)
0
16
0
Order By: Relevance
“…Basically, IDO1 is the initial enzyme that converts tryptophan to kynurenine which may lead to the production of neuroactive metabolites such as kynurenic acid (KA), 3-hydroxykynurenine (3-HK), and QUIN [26]. Recently, it has been reported that the kynurenine pathway becomes more active with age and the 3-HK level is positively associated with depression in nondemented women over 50 years of age [27].…”
Section: Discussionmentioning
confidence: 99%
“…Basically, IDO1 is the initial enzyme that converts tryptophan to kynurenine which may lead to the production of neuroactive metabolites such as kynurenic acid (KA), 3-hydroxykynurenine (3-HK), and QUIN [26]. Recently, it has been reported that the kynurenine pathway becomes more active with age and the 3-HK level is positively associated with depression in nondemented women over 50 years of age [27].…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan (Trp), L-kynurenine (L-Kyn), and KYNA levels were measured by an HPLC (high-performance liquid chromatography) method with fluorescence detection. 18 Briefly, 20 μL of serum supernatant sample were injected onto an Eclipse XDB-C18 reverse phase column (5-μm, 4.6 × 150 mm), and isocratically eluted with a mobile phase consisting of 50 mM sodium acetate, 250 mM of zinc acetate, and 3% of acetonitrile, pH adjusted to 6.2 with glacial acetic acid, at a flow rate of 1 mL/min; L-Kyn was eluted with the same mobile phase but without acetonitrile. KYNA was detected at excitation wavelength: 344 nm, emission wavelength: 398 nm, and L-Kyn at excitation wavelength: 368 nm, emission wavelength: 480 nm.…”
Section: Measurement Of Serum Kynureninesmentioning
confidence: 99%
“…The 3HK levels were determined using an electrochemical method. 18 Briefly, 40 μL of sample were injected onto a Adsorbosphere Catecholamine C18 reverse phase column (3 μm, 4.6 mm × 100 mm) and eluted at a constant flow rate of 0.6 mL/min with a mobile phase containing 9% of triethylamine, 0.59% phosphoric acid, 0.27 mM ethylenediaminetetraacetic acid (EDTA), and 8.9 mM heptane sulfonic acid. The retention time was ~11 minutes.…”
Section: Measurement Of Serum Kynureninesmentioning
confidence: 99%
“…Apart from animal studies, data derived from human populations have also revealed a significant correlation between elevated serum KYN/L-TRP ratio (indicative of inflammation-driven KP induction) and a progressively poor cognitive function [69,70]. A possible association between aging and raised KYN/L-TRP ratio, accompanied by a poor mental capacity, was first hinted by Ramos-Chávez et al [71]. Besides KYN/L-TRP, a progressively rising KYNA/QUIN ratio has also been strongly linked with a poor cognitive performance in cases of schizophrenia.…”
Section: Involvement Of Kp Metabolites In Neurocognitive Impairmentmentioning
confidence: 99%